Effects of oil palm plantation development on peat physical properties of secondary peat swamp forest in Igan, Sarawak, Malaysia - Firdaus, Mohd Suffian (2011)
There are several activities related to oil palm plantation development on peat land such as drainage, land clearing, biomass management, earthworks and planting. These activities inevitably change the physical properties of the peat soil and lead to the changes on other soil properties which are contributing to peat land degradation. Therefore, it is important to investigate the degradation severity of secondary peat swamp forest caused by the conversion to oil palm plantation in terms of its peat soil physical properties. This study was conducted in a drained secondary peat swamp forest (DSPSF) at Igan, Sibu, Sarawak, Malaysia. Soil sampling and data collection were done in 300 m2 experimental plots of drained secondary peat swamp forest and cleared site of the DSPSF, young oil palm plantation (YOPP) and mature oil palm plantation (MOPP). In each site, thirty random data points were used to measure saturated hydraulic conductivity, soil bearing capacity and surface soil temperature. Thirty undisturbed cores and bulk samples were also collected randomly for laboratory analysis of bulk density, specific gravity, gravimetric and volumetric water content, fiber content, loss on ignition, ash content, liquid limit and total porosity. After the draining, land clearing was done to remove the remaining vegetation before the peat land will be prepared for oil palm planting process. Therefore, the first part of this study was to determine the effect of land clearing on the selected peat soil physical properties of the DSPSF. Drainage in the secondary peat swamp forest decreased the fibre content, gravimetric water content, loss on ignition, total porosity and surface soil temperature. After the land clearing, gravimetric water content, liquid limit and total porosity continued to decrease, while surface soil temperature increased as well as ash content, bulk density and bearing capacity. However, fiber content, volumetric water content, specific gravity and saturated hydraulic conductivity in the DSPSF were not affected. Climate could influences the changes of peat soil physical properties and it related to the disturbance occurred on the peat land. Therefore, the second part of the study was to determine whether local climate influences peat soil physical property changes in the DSPSF and cleared site of the DSPSF. In this study, soil sampling and data collection were done under humid and dry season of the local climate. In DSPSF, volumetric water content, ash content and bulk density were significantly higher under the dry season while loss on ignition and total porosity were significantly higher under the humid season. The other properties were statistically similar between the two seasons. In the cleared site of DSFSF, bulk density was significantly higher under the dry season while gravimetric water content and total porosity were significantly higher in the humid season. The other properties were statistically similar between the two seasons. After clearing the DSPSF, the land preparation for oil palm planting and fertilizer application will continuously change the peat soil physical properties. Therefore, the third part of the study was to compare the peat soil physical properties of DSPSF and YOPP. Two years after oil palms planting have continuously increased surface soil temperature, bulk density, ash content and bearing capacity as well as continuously decreased loss on ignition, liquid limit, total porosity and saturated hydraulic conductivity. However, fiber content (degree of decomposition), gravimetric and volumetric water content and specific gravity were not affected. The effect of the conversion on peat soil physical properties probably prolonged after the oil palm plantation establishment. Therefore, the last part of this study was to compare selected peat soil physical properties of YOPP and MOPP. Peat soil decomposition was continued after the oil palm plantation has been established. The decomposition process was enhanced by the lower water table and increase of mineral content (ash content) in YOPP. Increase of degree of decomposition of peat soil and higher fertilization rate in the MOPP caused continuous increase of bulk density and ash content as well as continuous reduction of fiber content, loss on ignition, total porosity and liquid limit. However, high water table in the MOPP has reduced the bearing capacity and restored the water content in the peat soil. For the conclusion, developing oil palm plantation on secondary peat swamp forest increased the decomposition rate of peat soil which caused increase of degree of decomposition and volumetric water content, reduction of loss on ignition and liquid limit as well as increase of ash content due to the increase rate of mineralization and fertilizer application. The soil compaction and the reduction of organic matter content caused by the development also increased the bulk density and reduced the total porosity. Gravimetric water content, surface temperature and bearing capacity were increased after the land clearing but then decreased after the plantation was established and the effects were more influenced by the environment factors. Effect of the development on saturated hydraulic conductivity was hardly to determine due to the presence of partially decomposed residues in the peat soil. The changes occurred on the selected peat soil physical properties indicated that the peat soil was undergoing a process of degradation.